Identification of Minimum Data Set Under Balanced Fertilization for Sustainable Rice Production and Maintaining Soil Quality in Alluvial Soils of Eastern India. Issue 18 (11th October 2017) - Singh, Shiv Ram; Kundu, Dilip Kumar; Dey, Pradip; Mahapatra, Bikash Singha
ABSTRACT: The scarcity of non-renewable fertilizers resources and the consequences of climate change can dramatically influence the food security of future generation. Introduction of high yielding varieties, intensive cropping sequence and increasing demand of food grains day-by-day, application of recommended dose of fertilizers could not fulfill our targets due to outdated fertilizers recommendations are yet in practice. It not only alters soil quality, nutrient balance, microbial and enzymatic ecology but also affected productivity and sustainability of rice in Gangetic alluvial soils of India. The effect of fertilizers application based on "fertilizing the soil versus fertilizing the crop" which insure real balance between the applied and available soil nutrient is urgently needed. Hence, the present study was conducted during three consecutive crop seasons (2010, 2011, and 2012) to assess the effect of imbalance and balance fertilization based on initial soil test values and targeted yields, and to determine the effect of farmyard manure (FYM) when superimposed with balanced fertilizers on identification of minimum data set for the development soil quality, nutrient acquisition, and grain yield of rice. The six fertilizer treatments were laid out in a randomized block design with three replications. The treatments were: T1 -control (no fertilization), T2 -farmyard manure @ 5 t ha −1, T3 -farmers practice (60:30:30 kg N:P2 O5 :K2 O ha −1 ), T4 -precise application of mineral fertilizers based on initial soil test values (77:24:46 kg N:P2 O5 :K2 O ha −1 ) for targeted grain yield of 4.0 t ha −1, T5 -precise application of mineral fertilizers based on initial soil test values (74:23:43 kg N:P2 O5 :K2 O ha −1 ) plus FYM (5 t ha −1 ) for targeted grain yield of 4.0 t ha −1 and T6 -precise application of mineral fertilizers based on initial soil test values (135:34:65 kg N:P2 O5 :K2 O ha −1 ) for targeted rice grain yield of 5.0 t ha −1 . Result revealed that the targeted rice grain yield of 4.0 and 5.0 t ha −1 was achieved in T4 and T6 treatments with 1.59% (4.06 t ha −1 ) and –3.40% (4.83 t ha −1 ) deviations, respectively. T4, T5, and T6 significantly increased crop growth, nutrient uptake, available P (Pa ) and K (Ka ) and augmented rice grain yield by 10.6, 20.2 and 31.6%, respectively, over T3 . Microbial biomass carbon, soil respiration and enzymatic activity were enhanced significantly in T5 as compared to T6 . Highest soil quality index was found in T5 (0.95) followed by T6 (0.90) and, lowest was in T1 (0.63). The contribution of minimum data set (MDS) toward the SQI was in the descending order of ALP (30.6%) > SOC (21.5%) > Ka (11.3%) > PSM (9.68%) > Na (8.51%). Overall, rice yield and soil quality was improved by using balance fertilization based on fertilizing the crop V s fertilizing the soil in alluvial soils of India.